IN SITU RAMAN SPECTROSCOPIC STUDY OF SULFUR-SATURATED WATER AT 1000 BAR BETWEEN 200 AND 500°C - Bondarenko G.V.; Gorbaty Yu.E. (My University, 1997)
Raman spectra of a hydrothermal fluid, interacting with elementary sulfur, have been measured in the temperature range from 200 up to 500°C at a constant pressure of 1000 bar. The main products of the interaction are H2S, SO2, [HSO4]−, and S0. The temperature dependencies of intensities for characteristic Raman lines of these species have been found. They show that concentrations of H2S and SO2 behave much alike, increasing in the whole temperature range studied, whereas the temperature trends for [HSO4]− and S0 show maxima at 350–400°C, so that these species practically disappear at higher temperatures. The temperature dependencies for all the main components of the solution reveal features around the critical isotherm at isobaric heating or cooling. At low temperatures, the presence of the [SO4]2− ion may be suspected. The ion [HS]− exists in the whole temperature range. Also, weak bands of the anion [S2O3]2− seem to occur in the spectra.